1999
DOI: 10.1038/sj.ejcn.1600722
|View full text |Cite
|
Sign up to set email alerts
|

Yoghurt enriched with Lactobacillus acidophilus does not lower blood lipids in healthy men and women with normal to borderline high serum cholesterol levels

Abstract: Objective: To investigate whether intake of Lactobacillus acidophilus strain L-1 lowers serum cholesterol in healthy men and women. Design: Randomised, placebo-controlled parallel trial. Setting: Subjects were free-living. Blood sampling and distribution of yoghurts were administered at a local hospital. Subjects: Seventy-eight adult men and women with cholesterol levels of 3.9 ± 7.8 mmolaL (mean AE s.d., 5.4 AE 0.7). Interventions: Subjects consumed 500 mL of control yoghurt daily for two weeks. They were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(58 citation statements)
references
References 30 publications
4
52
1
1
Order By: Relevance
“…Investigations demonstrating a hypocholesterolemic effect have generally been conducted in subjects with moderately elevated (46.0 mmol/l) baseline TC (Agerback et al, 1995;Bertolami et al, 1999;Xiao et al, 2003;Hlivak et al, 2005) with the exception of one study with a mean TC of 5.2 mmol/l that included 9 g of fructo-oligosaccharide (a potentially hypocholesterolemic ingredient) in the fermented milk. In contrast, baseline TC in studies that did not show a hypocholesterolemic effect tended to be lower (o5.4 mmol/l) (de Roos et al, 1999;Greany et al, 2004) although a recent investigation in subjects with a mean TC of 6.6 mmol/l (Lewis and Burmeister, 2005) also failed to document a lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Investigations demonstrating a hypocholesterolemic effect have generally been conducted in subjects with moderately elevated (46.0 mmol/l) baseline TC (Agerback et al, 1995;Bertolami et al, 1999;Xiao et al, 2003;Hlivak et al, 2005) with the exception of one study with a mean TC of 5.2 mmol/l that included 9 g of fructo-oligosaccharide (a potentially hypocholesterolemic ingredient) in the fermented milk. In contrast, baseline TC in studies that did not show a hypocholesterolemic effect tended to be lower (o5.4 mmol/l) (de Roos et al, 1999;Greany et al, 2004) although a recent investigation in subjects with a mean TC of 6.6 mmol/l (Lewis and Burmeister, 2005) also failed to document a lipid-lowering effect.…”
Section: Discussionmentioning
confidence: 84%
“…Although most studies have reported a hypocholesterolemic effect (Agerback et al, 1995;Schaafsma et al, 1998;Bertolami et al, 1999;Xiao et al, 2003), not all investigations support this result (Richelsen et al, 1996;de Roos et al, 1999). The logistics of procuring and storing a fermented milk product for daily consumption and the dietary modification required to accommodate the additional calories contained in fermented milk products have prompted an exploration of alternative methods for ingesting probiotic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies investigated the cholesterol-lowering effect in hypercholesterolaemic patients or after a high-fat diet (Bertolami et al, 1999;Kawase et al, 2001;Doncheva et al, 2002;Abd El-Gawad et al, 2005). There are few reports documenting the influence on normocholesterolaemic subjects (De Roos et al, 1999;Jahreis et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19] The majority of randomized controlled trials, however, have reported no significant effect, [20][21][22][23][24][25] and no clinical trial has reported significant LDL-C reductions of a probiotic supplement formulation unless delivered as a synbiotic. 26 Previously, we have reported on the cholesterollowering efficacy of a microencapsulated BSH-active Lactobacillus reuteri NCIMB 30242 yogurt formulation.…”
Section: Introductionmentioning
confidence: 99%